The level of job satisfaction among administration officers in Public University / Nurul Asyikin Mohd Isa - Mohd Isa, Nurul Asyikin (Faculty of Business and Management, 2016)
Project paper titled “The level of Job Satisfaction among administration officer in public university” is conducted as partial requirement to fulfil the requirement as needed by the faculty of Business Management, MARA University of Technology (UiTM). According to Spector (1997), job satisfaction is defined as the “extent to which a person likes (satisfaction) or dislikes (dissatisfaction) his / her job”. The primary objective of this study is to identify the level of job satisfaction among administration officer in public university. Then this study also to study on the relationship between Salary Satisfaction, My Supervisor, My Peers, Promotion Opportunities, and Work Itself and Job Satisfaction among administration officer in public university. The sample group (N=50) consist to administration officer in public university. Results indicate that employees in public university are at high level of job satisfaction.